The Effect of an advanced nurse practitioner led menopause clinic on quality of life and menopausal symptoms - Catriona Keye (Women's Health)
Background: Research suggests women feel there is a lack of information and support around menopause leading them to be unprepared for the transition. Menopause care requires the practitioner to provide women with accurate information regarding symptoms and treatment. Advanced nurse practitioners (ANPs) have been found to have the knowledge and skills to provide high-quality, safe, individualized holistic healthcare. An ANP-led menopause clinic was established following intense mentorship/competency assessment and completion of industry standard courses to ensure evidence-based best practice. Objectives: To evaluate any change in quality of life (QoL) and menopause symptoms of patients pre- and post-education and initiation of menopause hormonal treatment (MHT) using the QoL assessment tool, the Greene Scale in an ANP-led menopause clinic. Design: This interventional study was carried using GUIDED, Guidance for reporting intervention development studies in health research. This quantitative audit used the Greene Scale tool to measure symptoms and QoL before and after the appointment with the ANP. Methods: A search of the patient database was conducted to identify patients returning for the 3-monthly review post initial consultation and initiation of MHT ( n  = 15). Data were collected on the modified Greene Scale instrument. The sample was randomly selected by identifying every second patient on a single medical surgery database. Statistical analysis was ascertained utilizing central tendency excel functionality. The statistical significance of the data was assessed using a two-tailed paired t -test. p -values of less than 0.05 were considered statistically significant. Results: An ANP-led menopause clinic in accordance with evidence-based guidelines, including education and treatment improved the overall QoL to a statistical significance. In addition, menopausal symptom reduction occurred in all 20 symptoms as measured in the modified Greene Scale, 19 of which to a statistical significance. Conclusion: The study revealed an improvement in QoL and menopausal symptoms in an ANP-led menopause clinic. ANP-led menopause clinics could be a great addition to the workforce providing patients with timely menopause care. Further studies could build on this analysis by including other variables such as comorbidities, demographics, and patient’s perspective.